Comparative analysis of the immediate results of thoracoscopic thymectomy using single-port and three-port approaches in the treatment of non-invasive epithelial thymic tumors - E. A. Epifantsev; A. V. Smirnov; V. Yu Gritsun; A. A. Keshvedinova; Yu. V. Ivanov (Исследования и практика в медицине)
Purpose of the study. Evaluation of the safety and effectiveness of single-port thoracoscopic thymectomy in comparison with traditional three-port thymectomy in patients with stage I and II thymic epithelial tumors.Patients and methods. The results of 50 thoracoscopic thymectomies performed from January 2019 to May 2023 on patients with stage I and II thymic epithelial tumors without the presence of myasthenia were analyzed. The age of the patients ranged from 20 to 75 years, with a median of 44 years. There were 28 (56 %) women, 22 (44 %) men. The minimum size of the removed thymoma in the study was 20 mm, the maximum was 165 mm. Out of the 50 patients who underwent singleand three-port thoracoscopic thymectomy, 42 (84 %) had tumor diameters of 70 mm or less, and 8 (16 %) had tumor diameters greater than 70 mm. Tumor size was significantly larger in the three-port thymectomy group (43 mm [35 mm; 55 mm] vs. 60 mm [38 mm; 78 mm], p = 0.044).Results. The analysis noted a statistically significant increase in the duration of the operation in the group of three-port thoracoscopic thymectomies (duration of operations – 107.5 minutes [70 minutes; 132.5 minutes] versus 70.0 minutes [57 minutes; 79 minutes] in the group with a single-port approach). A statically significant result was also obtained in terms of drainage of pleural cavity drainage and, as a consequence, in duration of postoperative bed rest. Patients operated through a single-port approach stayed in the hospital for 3 to 5 days on average (4.0 days), while those with a three-port approach stayed from 3 to 13 days on average (5.0 days). A comparative analysis revealed a significant reduction in the length of hospital stay in patients who underwent single-port thoracoscopic thymectomy, in contrast to those undergoing three-port surgical interventions.Conclusion. This study is the first in Russia to compare oneand three-port techniques for removing thymic tumors in a number of patients sufficient for statistical calculations. It has been shown that for thymic tumors up to 5 cm, single-port thoracoscopic thymectomy compared to three-port does not lead to prolongation of the operation or an increase in intraand postoperative complications. Therefore, in our opinion, it is the preferable option.